Hydrogen-Rich Saline Attenuates Acute Renal Injury in Sodium Taurocholate-Induced Severe Acute Pancreatitis by Inhibiting ROS and NF-κB Pathway - Qiao Shi; Kang-Shu Liao; Kai-Liang Zhao; Wei-Xing Wang; Teng Zuo; Wen-Hong Deng; Chen Chen; Jia Yu; Wen-Yi Guo; Xiao-Bo He; Ablikim Abliz; Peng Wang; et al. (Mediators of Inflammation)
Hydrogen (H2), a new antioxidant, was reported to reduce •OH and ONOO− selectively and inhibit certain proinflammatory mediators to product, without disturbing metabolic redox reactions or ROS involved in cell signaling. We herein aim to explore its protective effects on acute renal injury in sodium taurocholate-induced acute pancreatitis and its possible mechanisms. Rats were injected with hydrogen-rich saline (HRS group) or normal saline (SO and SAP group) through tail intravenously (6 mL/kg) and compensated subcutaneously (20 mL/kg) after successful modeling. Results showed that hydrogen-rich saline attenuated the following: (1) serum Cr and BUN, (2) pancreatic and renal pathological injuries, (3) renal MDA, (4) renal MPO, (5) serum IL-1β, IL-6, and renal TNF-α, HMGB1, and (6) tyrosine nitration, IκB degradation, and NF-κB activation in renal tissues. In addition, it increased the level of IL-10 and SOD activity in renal tissues. These results proved that hydrogen-rich saline attenuates acute renal injury in sodium taurocholate-induced acute pancreatitis, presumably because of its detoxification activity against excessive ROS, and inhibits the activation of NF-κB by affecting IκB nitration and degradation. Our findings highlight the potential value of hydrogen-rich saline as a new therapeutic method on acute renal injury in severe acute pancreatitis clinically.